Pengelolaan Koperasi Canggu Beach Transport Sebagai Wadah Pengusaha Angkutan Umum Pariwisata di Echo Beach Canggu Badung - Sumiati, Ni Made; Anom, I Putu (JURNAL DESTINASI PARIWISATA, 2018)
The growth of tourism industry is a push to growth of community’s creativity in developing their potential, by utilizing the opportunities created from the presence of tourism, such as tourism public transport services that is created by Koperasi C anggu Beach Transport. This study aims to know the management applied as well as the strenght and weakness of implementation . The research method that used to identify the management of tourism public transport service in C anggu is qualitative data and quantitative data obtained using the tec h niques of observation, inter vi ew and literature study . Purposive sampling is used to determine the informants . The result of this study concluded that the management of Koperasi Canggu Beach Transport has been appropriate according to planning and organizing which done before. Monthly meetings are held in an effort to control and evaluate the result of the project that already done. There are some suggestions to create new queue system that applied and also needed an increasement of socialization through social media to introduce and also as a promotion media . .   Keywords : Tourism, Management,Tourism Transport Mode,Transportation